Representations of inclusiveness in social assistance programmes of the 10th Malaysia Plan, 2011–2015 - Varghese, Mary; Gomez, Edmund Terence (Taylor & Francis, 2019)
This article appraises constructions of inclusiveness in social assistance programmes in the Malaysian socioeconomic agenda of the 10th Malaysia Plan, 2011–2015 (10MP). Setting as context the needs-based aspirational inclusiveness articulated in documents preceding the 10MP, this study adopts a discursive approach to probe the realisations of such inclusiveness in the 10MP. The analysis reveals essentialised ethnic constructions of different communities and their needs, as well as differing degrees of commitment in initiatives proposed, thereby indicating the slippage in discourse between the aspirations of inclusiveness and their realisations in actual initiatives in the 10MP. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.